The Philosophy of Pancasila Communication Ethics: A Literature-Based Approach to Communication Ethics (Oratio Directa, 2020)
Communication ethics is essential for determining the quality of communication and interaction at both the individual and national levels. This article examines the procedural and substantive values underlying Indonesian communication ethics based on Pancasila. It applies a qualitative literature-review method using books and documents on Pancasila philosophy, values, implementation, and communication ethics. The analysis shows that the ontological, epistemological, and axiological foundations of Pancasila position communication as both a natural right and an obligation. Communication should therefore be religious, humane, just, civilized, solidaristic, dialogical, rational, and responsible. Pancasila communication ethics can provide a normative framework for civilized communication amid technological change and the transformation of the media industry.
Keywords: Pancasila philosophy; Communication ethics; Pancasila ideology; Civilized communication; Communication media